ANALYSIS OF UPPER LIMB KINEMATICS IN VERTICAL JUMP SHOTS IN HANDBALL - Singh, Karam Shyamananda; Singh, Laishram Thambal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Background: The kinematic analysis of jump shot with reference to the analysis of the release angle of different joints of the arm helps us to understand how to improve the maximal force muscles produced where the motor actions are performed at that instant frame of release. Objective: The main objective was to investigate, assess and compare the angle of release of different joints of the right arm among handball players (Under-16 and Under-18). Methodology: Thirty right handed national-level handball players (15 players of under-16 and 15 players of under-18) were selected by employing a stratified random sampling technique so that the possibilities of selection of players from each position were uniform. For measuring the angle of release of different joints of the right arm (wrist joint, elbow joint and shoulder joint) at the instant frame of the handball released, a high-speed action camera (GoPro 12) was used for capturing the frame for this study. Kinovea, a video annotation tool designed for sports analysis was used for record and further investigation and analysis of the angle of the joints of the right arm. Result and Conclusion: Significant differences were found among the two groups of their means comparison of the shoulder joint (P<0.05), but there were no significant contrasts in the elbow and wrist joints of the two groups which were considered for the study (P>0.05). The following result could give a few conclusions regarding the speed generated by the groups and injuries could be identified in future by studying the range of movements.